The ABC membrane transporter ABCG2 prevents access of FAAH inhibitor URB937 to the central nervous system - Moreno-Sanz, Guillermo (2011)
The O-arylcarbamate URB937 is a potent inhibitor of fatty-acid amide hydrolase (FAAH), an intracellular serine hydrolase responsible for the deactivation of the endocannabinoid anandamide. URB937 is unique among FAAH inhibitors in that is actively extruded from the central nervous system (CNS), and therefore increases anandamide levels exclusively in peripheral tissues. Despite its limited distribution, URB937 exhibits marked analgesic properties in rodent models of pain. Pharmacological evidence suggests that the extrusion of URB937 from the CNS may be mediated by the ABC membrane transporter ABCG2 (also called Breast Cancer Resistance Protein, BCRP). In the present study, we show that URB937 is a substrate for both mouse and human orthologues of ABCG2. The relative transport ratios for URB937 in Madin-Darby canine kidney (MDCKII) cells monolayers over-expressing either mouse Abcg2 or human ABCG2 were significantly higher compared to parental monolayers (13.6 and 13.1 vs 1.5, respectively). Accumulation of the compound in the luminal/apical side was prevented by co-administration of the selective ABCG2 inhibitor, Ko-143. In vivo studies in mice showed that URB937 (25 mg-kg(−1)) readily entered the brain and spinal cord of Abcg2-deficient mice following intraperitoneal administration, whereas the same dose of drug remained restricted to peripheral tissues in wild-type mice. By identifying ABCG2 as a transport mechanism responsible for the extrusion of URB937 from the CNS, the present results should facilitate the rational design of novel peripherally restricted FAAH inhibitors.